2018
DOI: 10.3389/fneur.2018.00880
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolated PAS-Positive Lymphocytes on Blood Smear: An Easy Screening Tool and a Possible Biomarker for Monitoring Therapeutic Responses in Late Onset Pompe Disease (LOPD)

Abstract: Background: Primary aim was to investigate the diagnostic value of PAS-positive vacuolated lymphocytes on blood smear in Late Onset Pompe Disease (LOPD) patients and, secondly, to evaluate its potential utility in monitoring treatment effects.Methods: We examined blood smear of 26 LOPD patients. We evaluated 10 treated and 16 untreated LOPD patients. Among the latter group, 7 patients later initiated ERT and were tested again 6 months after start. Blood smear was also sampled from 82 controls and 19 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that assessing vacuolated lymphocytes in a blood smear is a potent marker in diagnosing autophagic myopathies ( 34 ). It can be considered a possible biomarker, and some authorities advise ordering blood smear examination to be performed even before GAA assay in DBS ( 35 ). Blood smear examination results need to be established by the finding of enzyme deficiency ± genetic analysis.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…It has been demonstrated that assessing vacuolated lymphocytes in a blood smear is a potent marker in diagnosing autophagic myopathies ( 34 ). It can be considered a possible biomarker, and some authorities advise ordering blood smear examination to be performed even before GAA assay in DBS ( 35 ). Blood smear examination results need to be established by the finding of enzyme deficiency ± genetic analysis.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…The number of PASpositive lymphocytes in treated and untreated patients is quite different; although a small number of patients were studied, the difference was significant, suggesting that quantification of vacuolated lymphocytes on BSE can be considered a possible biomarker in therapeutic trials. These data suggest that BSE could be performed as a blood-based method in screening programs even before GAA assay in DBS which is a more sophisticated technique and not available in all diagnostic laboratories (19). However, BSE results need to be confirmed by the detection of enzyme deficiency and/or genetic analysis.…”
Section: Quantification Of Lymphocytes With Glycogen-filled Vacuoles mentioning
confidence: 99%
“…Detection of lymphocytes with vacuoles filled with glycogen in the blood smear (BSE; blood smear examination) has been suggested as a useful tool for Pompe diagnosis (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Double GAA pathogenic mutations represent the final diagnostic confirmation of GSDII. Although muscle biopsy remains an important tool in the evaluation of muscle disorders, including GSDII, counting of vacuolated Periodic Acid-Schiff (PAS)-positive lymphocytes in blood smears has been proposed as a fast screening test to identify LO-GSDII, as well as for monitoring the efficacy of enzyme replacement therapy (ERT) treatment with recombinant human α-glucosidase (rGAA) [8,10]. We recently proposed an algorithm for the diagnosis of myopathies related to impaired autophagy.…”
Section: Introductionmentioning
confidence: 99%